Hak Anak Dalam Prinsip Bisnis di Industri Hotel - Mustika Permatasari; Dony Riyadi; Mega Aldora (Politeknik Pariwisata Makassar, 2021)
The city of Bandung and Subang are tourist attractions that offer a variety of entertainment, especially for family tourists in spending their vacation time. In supporting comfort and service so that tourists spend their time, it is necessary to support facilities ranging from hotels and restaurants that not only offer services for adult guests but also for children. The presence of children's guests is still often considered a minority by hoteliers. This can be seen from several hotels that have not considered the children's menu and facilities in the form of products or services that provide a sense of comfort and safety. This research is a descriptive quantitative study with a sample of hotels in Bandung and Subang where guests are family. The purpose of this study was to see how important the menu and facilities of children owned by hotel entrepreneurs in the City of Bandung and Subang. The results of this study indicate that hotel guest expectations regarding hotel services and facilities have an interval value of> 4.21, which means it is very important. Ratings with the highest scores are inclined to attributes of swimming pools and water parks, children's activities and play spaces as well as complete children's menus.